Customer Ethnic Bias in Service Encounters. (May 2020) - Linzmajer, Marc; Brach, Simon; Walsh, Gianfranco; Wagner, Tillmann
As ethnic diversity continues to rise, customer bias in interethnic service encounters becomes an increasingly problematic issue for the parties involved, the service firms, and society at large. Against this background, the aim of our research is to examine ethnically biased customer responses, their key psychological mechanisms, and the effectiveness of enacted service scripts to shape interethnic service encounters. Building on the aversive racism framework and homophily theory, we propose a baseline effect of majority customers' ethnic bias toward minority employees in the form of less positive behaviors in interethnic service encounters. In an initial laboratory study, we use experimental video simulations of frontline service encounters and confirm the robustness of this effect across two replications. In a subsequent field experiment, we test an extended framework of customer responses to interethnic service encounters, finding that customers' experience of rapport and identification with the firm represent two serial mediators that facilitate the effects of interethnic service encounters on customer loyalty intentions. Together, these contributions enrich our understanding of how psychological mechanisms facilitate the incidence of ethnically biased customer behavior and also provide insights into viable ways to improve such encounters.